2015
DOI: 10.1021/nn5066606
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cytotoxicity of Graphene Nanosheets Mediated by Blood-Protein Coating

Abstract: The advent and pending wide use of nanoscale materials urges a biosafety assessment and safe design of nanomaterials that demonstrate applicability to human medicine. In biological microenvironment, biomolecules will bind onto nanoparticles forming corona and endow nanoparticles new biological identity. Since blood-circulatory system will most likely be the first interaction organ exposed to these nanomaterials, a deep understanding of the basic interaction mechanisms between serum proteins and foreign nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
224
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(245 citation statements)
references
References 81 publications
17
224
1
3
Order By: Relevance
“…Bacteria cells were rst grown overnight in LB medium (LuriaBertani) at 37 C and harvested at the mid-exponential growth phase via centrifugation. Then they were washed three times to remove the residual growth-medium constituents and resuspended in the sterile saline solution (0.9% NaCl).…”
Section: Bacterial Cell Preparation and Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria cells were rst grown overnight in LB medium (LuriaBertani) at 37 C and harvested at the mid-exponential growth phase via centrifugation. Then they were washed three times to remove the residual growth-medium constituents and resuspended in the sterile saline solution (0.9% NaCl).…”
Section: Bacterial Cell Preparation and Antibacterial Activitymentioning
confidence: 99%
“…45 Briey, A549 cells and HEP G2 cells were seeded in a 96-well cell culture plates at the densities of 5 Â 10 3 cell per well, respectively, in DMEM containing 10% FBS at 37 C in a humid atmosphere of 95% air and 5% CO 2 for 24 h. Aer 24 h incubation, cells reached $80% conuence. Subsequently, the cells were incubated with WS 2 in serum-free medium, following a similar protocol used in our previous studies, 37 with WS 2 concentrations 12.5, 25, 50, 100, and 200 mg mL À1 . The cells cultured in the medium without any nanomaterials were used as the control.…”
Section: In Vitro Cytotoxicity To Eukaryotic Cellsmentioning
confidence: 99%
“…A previous report have shown that GO adheres to the chorion of the zebrafish embryo mainly via hydroxyl group interactions and crosses the chorion of the zebrafish through independent pore canals via passive diffusion 15. At 72 hpf, the green fluorescence denoted by the red circles was distributed to the head, eyes, gills, heart, intestines, and yolk sac edema of the larvae treated with the FITC‐GOQDs, suggesting that the GOQDs were predominantly distributed to these regions (Figure 4a), especially in the heart and intestines because the blood circulatory system would most likely be the first organ to be exposed to carbon‐based nanoparticles16 and because swallowing into the intestines is also a common pathway for absorbing nanoparticles. [[qv: 5b]] However, the green fluorescence denoted by the red circles was only distributed in the yolk sac edema of the larvae treated with FITC, indicating that the GOQDs and FITC concentrated in different regions within the larvae (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] For example, a recent study investigated the adsorption of the four most abundant serum proteins, i.e., bovine serum albumin (BSA), transferrin (Tf), immunoglobulin (Ig), and bovine fibrinogen (BFG) on two graphene nanomaterials, i.e., GO and rGO nanosheets (Fig. 3).…”
Section: Interactions Of Graphene Nanomaterials With Serum Biomomentioning
confidence: 99%
“…3). 47 It was reported that these proteins displayed distinct adsorption behaviors on the nanosheet surfaces. BSA, for instance, formed complex aggregates upon its first interaction with GO [ Fig adsorption on the GO surface was enthalpically driven via hydrophobic interactions and essentially, strong p-p stacking interactions between the aromatic protein residues and GO surface.…”
Section: Interactions Of Graphene Nanomaterials With Serum Biomomentioning
confidence: 99%